Optical Coherence Tomography and Glaucoma Progression: A Comparison of a Region of Interest Approach to Average Retinal Nerve Fiber Layer Thickness. Issue 5 (May 2017) - Thenappan, Abinaya; De Moraes, Carlos Gustavo; Wang, Diane L.; Xin, Daiyan; Jarukasetphon, Ravivarn; Ritch, Robert; Hood, Donald C.
Abstract : Purpose: To determine whether the change in the retinal nerve fiber layer (RNFL) thickness in a region of interest (ROI) is a better measure of glaucoma progression than the change in average circumpapillary (cp) RNFL thickness. Methods: Disc cube scans were obtained with frequency domain optical coherence tomography from 60 eyes of 60 patients (age, 61.7±12.7 y) with early or suspected glaucoma and controlled intraocular pressure. The average time between 2 test dates was 3.2±1.8 years. En-face images of the scans from the 2 tests were aligned based on the blood vessels, and cp images were derived for an annulus 100 μm wide and 3.4 mm in diameter, centered on the disc. An ROI was defined as the portion of the circumpapillary retinal nerve fiber layer (cpRNFL) plot within the temporal disc that extended below the 1% confidence interval for ≥5 degrees. Trend analysis using multilevel mixed-effects models was used to compare the rates of change between ROI width and average cpRNFL thickness. Results: In total, 26 of the 60 eyes had a total of 33 ROIs. The ROI width significantly increased between the 2 test dates (median, 4.9 degrees; Q1=1.03 degrees, Q3=10.5 degrees). In comparison, the average cpRNFL thickness did not decrease significantly over the same period (median, −0.7 μm; Q1=−2.7 μm, Q3=2.7 μm). Mixed-effects linear models confirmed significant ROI progression ( P =0.015), but not average cpRNFL ( P =0.878). Conclusions: In this population, RNFL thinning in a ROI is a better measure of progression than is average cpRNFL thickness change.